Optimization of house construction project planning using PERT and CPM - Rahyuni Chania; Gesit Thabrani (Universitas Negeri Padang, 2022)
Scheduling in the project plan is the determination of the network and the time required for each activity to complete the project. Some of the problems in project planning in project management are non-scheduling, delays, and swelling costs that are detrimental to project contactors and reduce customer satisfaction. The type of research is descriptive research. The research was conducted in Nagari Ladang Panjang, Kec. Tigo Nagari Kab. Pasaman Prov. West Sumatra with secondary data obtained from 10 housing construction units of type 36 through interviews. Scheduling optimization is carried out using the CPM (critical path method) method with ES, EF, LS, LF, and the PERT (program evaluation review technique) method based on 3 estimated time and project completion probabilities based on the standard Z value. From the results of research conducted after scheduling using PERT /CPM and crashes on 3 activities, project completion can be done in 29 days at 47,445,781 IDR. For project completion using PERT/CPM, which is 38 days. Meanwhile, before scheduling (actualization) the completion of the project took 41.5 days at 45,295,781 IDR.